Associative and Gender Aspects of the Emotional Concept of Jealousy in the Ukrainian Linguistic Culture - Petiak, Olena (East European Journal of Psycholinguistics, 2020)
The article deals with the associative and gender features of the perception by marriage partners of the emotional concept of "jealousy" within the framework of Ukrainian linguistic culture. Associative and gender features of the emotional concept of “jealousy” were found out as a result of data analysis of free word association test held with 100 Ukrainian speaking students, graduate students, and teachers (50 men and 50 women) at Khmelnytskyi National University (Ukraine). The respondents were in official marriage; their age was from 18 to 65. With the help of the free word association test the connections of the concept of "jealousy" in the Ukrainian language consciousness and the semantic zones of this stimulus word were determined. An important step was to take into account the opinions of the researchers regarding the possible difference between manifestations and the emergence of jealousy in men and women. Psycholinguistic ideas about jealousy are manifested in the ambivalence of emotions, the semantic signs of which are the polar properties of “love” (“care”) – “hatred” (“doubt”, “suspicion”). The gender factor affects the structure of the associative field of the concept of "jealousy" and determines both the quantitative indicators in the structure of the organization of the associative field of the concept, as well as its “semantic content”. Qualitative analysis of the results of the free association test helped to form separate fragments of male and female world images in their linguistic consciousness and made it possible to talk about gender stereotypes regarding jealousy in the everyday linguistic consciousness of marriage partners.